MayaLense Studio Sdn Bhd / Abdullah Ismail... [et al.] - Ismail, Abdullah; Ahmad, Kamarul Arifeen; Suriansah, Nila; Robbert, Aloysia; Karim, Fahmi (Faculty of Business Management, Universiti Teknologi MARA, 2010)
The business is a photography-oriented business and offers a complete photography services such as taking photos. As one of the reason our business prepared this business plan is to attracts future investors who might wants to invest in the company's share, therefore, the company other alternative source of financing is the future investors.